2012
DOI: 10.1021/jo2024976
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective α-Benzoyloxylation of Ketones Promoted by Primary Amine Catalyst

Abstract: A mixture of 9-amino-(9-deoxy)epi-dihydroquinidine and salicylic acid was able to promote the direct reaction of various cyclohexanones with dibenzoyl peroxide, thus affording the corresponding protected α-hydroxy carbonyl compounds in high yield and enantioselectivity. Interestingly the same catalytic salt was found to be active when 1-indanones derivatives were directly employed in the reaction with dibenzoyl peroxide furnishing chiral 1-oxo-2,3-dihydro-1H-inden-2-yl benzoates in high yields and enantioselec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…163 Using 10 mol% of quinine-derived organocatalyst C-103 and salicylic acid as an additive, the reaction proceeded in good yield with complete enantioselectivity. 163 Using 10 mol% of quinine-derived organocatalyst C-103 and salicylic acid as an additive, the reaction proceeded in good yield with complete enantioselectivity.…”
Section: View Article Onlinementioning
confidence: 99%
“…163 Using 10 mol% of quinine-derived organocatalyst C-103 and salicylic acid as an additive, the reaction proceeded in good yield with complete enantioselectivity. 163 Using 10 mol% of quinine-derived organocatalyst C-103 and salicylic acid as an additive, the reaction proceeded in good yield with complete enantioselectivity.…”
Section: View Article Onlinementioning
confidence: 99%
“…26 A mixture of 9-amino-(9-deoxy)epidihydroquinidine Ib and salicylic acid was employed by Bencivenni et al to promote the direct α-benzoyloxylation of various cyclic ketones 30 with dibenzoyl peroxide (Scheme 11). 27 Notably, 1.2 equiv. of solid Na 2 CO 3 was used to increase the reaction rate and maintain a good level of enantioselectivity by quenching the benzoic acid generated during the course of the reaction, affording the corresponding protected α-hydroxy carbonyl compounds 31 in high yields and enantioselectivities.…”
Section: α-Functionalization Of Carbonyl Compoundsmentioning
confidence: 99%
“…Similar transformations with stoichiometric amounts of chemical oxidants were performed using hypervalent iodine compounds, Bu 4 NI/ t -BuOOH, , manganese­(III) acetate, , lead­(IV) acetate, and iron­(III) salts . Benzoyloxylation of the β-dicarbonyl compounds by benzoyl peroxide is based on their preliminary transformation into enamines, copper complexes, or enolates. Methods for the intermolecular oxidative acyloxy-functionalization of β-dicarbonyl compounds by diacyl peroxides have been discovered. Concerning electrochemical intermolecular acetoxylation, it was found that anodic oxidation of enol acetates led to α-acetoxycarbonyl compounds. , …”
Section: Introductionmentioning
confidence: 99%